The Role of Legal Advisors in Criminal Case Settlement Process - Nynda Fatmawati Octarina; Umi Faridah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Since the enactment of Law No. 8 of 1981, LN. No. 76 of 1981, namely regarding the Criminal Procedure Code which came into force on December 31, 1981, the provisions contained in the HIR (Het Herzine Inlandsch Reglement) Staatsblad 1941 44 and all its implementing regulations are no longer valid. The values of Pancasila and the 1945 Constitution which are noble and uphold the existence of human rights also recognize the position and role of defenders which are implemented or further embodied in the Criminal Procedure Code, namely Law No. 8 The position and role of the defender are closely related to the rights of the suspect or defendant because the defender or legal advisor is present in the process of settling criminal cases precisely to assist and defend the rights of the suspect or defendant as regulated in the Criminal Procedure Code (KUHAP) A suspect who is suspected of committing a criminal act is not necessarily a guilty person, nor is a defendant charged with a criminal act not necessarily guilty because in our legal state recognizes the principle of "the presumption of innocence", so the suspect or defendant must be considered innocent. guilty before there is a judge's decision that already has permanent legal force. The presence of a defender in the settlement of a criminal case in addition to accompanying a suspect or defendant and defending him is also due to moral and juridical responsibility as one part of law enforcement officers who work together same as other law enforcers trying to find the material truth. In this criminal justice process, the provisions of Article 54 of the Criminal Procedure Code emphasize the rights of the suspect be accompanied by the defense or legal counsel at every level of examination, in other words, that the suspect or defendant has the right to have contact with the defender from the time of the preliminary examination until the time of the preliminary examination. examination in court.